2018
DOI: 10.1137/17m1159968
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and Error Analysis for the Scalar Auxiliary Variable (SAV) Schemes to Gradient Flows

Abstract: We carry out convergence and error analysis of the scalar auxiliary variable (SAV) methods for L 2 and H −1 gradient flows with a typical form of free energy. We first derive H 2 bounds, under certain assumptions suitable for both the gradient flows and the SAV schemes, which allow us to establish the convergence of the SAV schemes under mild conditions. We then derive error estimates with further regularity assumptions. We also discuss several other gradient flows, which can not be cast in the general framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(103 citation statements)
references
References 23 publications
0
103
0
Order By: Relevance
“…Introduction. Recently, the so-called scalar auxiliary variable (SAV) approach is developed in [17,18]. This approach is inspired by the invariant energy quadratization (IEQ) approach [21] but fixes most, if not all, of its shortcomings.…”
mentioning
confidence: 99%
“…Introduction. Recently, the so-called scalar auxiliary variable (SAV) approach is developed in [17,18]. This approach is inspired by the invariant energy quadratization (IEQ) approach [21] but fixes most, if not all, of its shortcomings.…”
mentioning
confidence: 99%
“…The generalized auxiliary variable introduced here is inspired by the scalar auxiliary variable (SAV) approach proposed by [38], and to a lesser extent, by the invariant energy quadratization (IEQ) method [44], both of which are devised for gradient flows; see also e.g. [37,20,8,49,27,28,47,45] (among others) for extensions and applications of these techniques. In SAV a scalar-valued auxiliary variable is defined, as the square root of the shifted potential energy integral.…”
Section: Introductionmentioning
confidence: 99%
“…Ones have shown that these strategies are general enough to be useful for developing energy stable numerical approximations to any thermodynamically consistent models, i.e., the models satisfy the second law of thermodynamics or are derived from the Onsager principle [31,32,57]. The convex splitting approach, scalar auxiliary variable, energy quadratization approach and other methods have been applied to the Cahn-Hillard model for crystal growth [15,18,19,24,38,41,43,44,47,50,57].…”
Section: Introductionmentioning
confidence: 99%